Efforts to Increase Awareness of Holistic Health Among Z Genertion in Urban Village K, Central Java - Ardani, Alvanindya Nafik; Asyanti, Setia (Universitas Muhammadiyah Surakarta, 2025)
Competitive sports involve complex dynamics and high pressure that can trigger anxiety, including among soccer players who have already competed at Dormitory X. Excessive anxiety has the potential to interfere with athletes' performance. This study aims to explore pre-match and in-match anxiety among soccer players, identify its causes, and determine the sources of anxiety experienced. Participants consisted of four main subjects (soccer athletes aged 12–17 years residing at Dormitory X) and two supporting subjects (coaches familiar with the athletes). Subjects were selected using purposive sampling with criteria including anxiety experience and involvement in matches in 2024. The research approach used was qualitative narrative, with data collection methods including interviews, observations, and documentation, analyzed using Miles and Huberman's analysis technique. The results showed that athletes experienced anxiety before and during matches, stemming from internal factors (such as self-doubt) and external factors (such as pressure from expectations). The anxiety management strategies used included thought regulation, behavior control, breathing techniques, and support from Asrama X through competition preparation and joint spiritual activities such as night prayers and reading the holy book (the Qur'an or the Bible). These strategies proved effective in reducing anxiety, as reflected in the athletes' achievements in the competition.